An event study on the importance of foreign portfolio investment, institutional investment and its impact on Dubai financial market - Moosawi, Nasser (2013)
The purpose of this study is to measure the effect of foreign and institutional investments on Dubai Financial Market. 519 trading sessions between June 2010 and June 2012 have been analysed using three measurement instruments. Logic tests, correlation matrix and regression analysis has been used to conduct the analysis. The study suggests that both foreign and institutional investments affect the overall market value and liquidity and there is strong positive relationship between the overall market value and foreign and institutional value. The study indicates that foreign and institutional investments has no impact on the general index of the market and the relation between them is independent